The Piano: A Psychoanalytic Approach to Movie as A Media of Reflective Teaching - Erna Wardani (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
Freud’s psychoanalytic approach has been one of the most controversial approaches to many fields of interest. Relating to education and educational psychology, this approach plays a significant role in modifying and enhancing one’s behavioral relationship among the educational elements like educators, parents, and students. Therefore, in many things, this approach has contributed a lot of inspiration in the development of education. In literary works, there seems to be a mutual fascination between psychoanalysis and literature whereas theory and approach, psychoanalysis explains literature and literature itself exploits psychoanalysis for creative purposes and works. Here, as a creative work, movie is considered literature because it can be interpreted and analyzed just like other written works of literature. As a learning instrument, movie evokes an affective domain that leads to changes in learning behavior and attitudes. Experiencing certain-themed movies can trigger particular reflective memories and reference toward events occurring on a daily basis and it can further strengthen the foundation for learning complex concepts like psychoanalysis.